A UHPC containing glass fiber and its preparation method and application

Through the modified aluminum-oxygen tetrahedral content of ultrafine glass fibers and the combined doping technology with steel fibers, the problem of insufficient durability of existing ultrafine glass fibers in high alkaline environments is solved, and the comprehensive performance of UHPC is significantly improved, especially in terms of crack resistance, impact resistance and durability.

CN119551953BActive Publication Date: 2025-04-25UNIV OF JINAN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510080573.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The existing ultrafine glass fibers have insufficient durability, poor dispersion and weak interface bonding in high alkaline concrete environments, resulting in significant decline in their performance in concrete, especially in micro-crack control, stress transmission path optimization and impact resistance improvement.

Method used

Modified ultrafine glass fibers by lithium oxide and sodium hydroxide to increase their aluminum-oxytetrahedral content and compounded with steel fibers into UHPC. The modified ultrafine glass fibers form chemically bonds with the concrete matrix through hydroxyl groups to optimize the structural performance of the interface transition zone.

Benefits of technology

It significantly improves UHPC's crack resistance, impact resistance and long-term durability, enhances the interface bonding between fiber and concrete matrix, improves the density and chemical corrosion resistance of concrete, and extends the service life of fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551953B_ABST
    Figure CN119551953B_ABST
Patent Text Reader

Abstract

The present invention relates to a UHPC containing glass fiber and a preparation method and application thereof, belonging to the technical field of new building materials. The preparation raw materials include the following components by mass: 400-500 parts of cement, 40-50 parts of silica fume, 600-800 parts of fine aggregate, 1000-1200 parts of coarse aggregate, 30-50 parts of steel fiber, 10-30 parts of glass fiber, 120-150 parts of water and 6-8 parts of water reducer; the glass fiber is a modified ultrafine glass fiber, which is modified by lithium oxide and sodium hydroxide. The modification treatment significantly improves the durability of ultrafine glass fiber in a high alkaline environment, solves the problem of rapid performance decline of traditional ultrafine glass fiber due to insufficient chemical stability, and comprehensively improves the crack resistance, impact resistance and long-term durability of UHPC from macro to micro.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new building materials, and specifically relates to a UHPC containing glass fiber and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Ultra-High Performance Concrete (UHPC) is a new type of cement-based composite material with ultra-high strength, high toughness and high durability. The high cement content in its mix leads to severe early shrinkage, which is a technical problem that needs to be faced in its engineering applications.

[0004] The sources of waste glass include beverage bottles, food cans, building materials, and automobile glass. Waste glass from different sources has different components. The pollution and quality issues of the waste glass itself limit its use in the manufacture of high-quality glass. How to efficiently utilize and process waste glass has become a problem that needs to be solved urgently.

[0005] In the prior art, the technical solution of adding ultrafine glass fibers to UHPC has improved the crack resistance, strength and toughness of concrete to a certain extent, but there are still many shortcomings. First, traditional ultrafine glass fibers are susceptible to corrosion in a high-alkaline concrete environment, and their chemical stability is insufficient, resulting in a significant decline in performance over time, which in turn affects the long-term durability of concrete. Secondly, ordinary ultrafine glass fibers have poor dispersibility in the concrete matrix, and fiber agglomeration is prone to occur, resulting in an uneven matrix and difficulty in fully exerting the reinforcement effect. In addition, the interfacial bonding force between the ultrafine glass fibers and the concrete matrix is ​​weak, mainly relying on physical adsorption or van der Waals forces, and failing to form a sufficiently strong chemical bonding interface. The performance of the interface transition zone (ITZ) is poor, which limits the improvement of the overall performance of concrete by ultrafine glass fibers. Especially in terms of microcrack control, stress transfer path optimization and impact resistance improvement, the effect of the prior art is still insufficient. Therefore, how to effectively modify ultrafine glass fibers, significantly improve their alkali resistance and dispersibility, enhance their interfacial bonding with the concrete matrix, and improve the comprehensive performance of UHPC through synergistic effects with other fibers has become a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a UHPC containing glass fiber and a preparation method and application thereof, and to modify waste glass to prepare reinforced ultrafine glass fibers with a higher content of alumina tetrahedrons. The reinforced ultrafine glass fibers are compounded with steel fibers in UHPC and have good crack resistance, strength and toughness.

[0007] In order to achieve the above object, the technical solution of the present invention is:

[0008] In a first aspect, a glass fiber UHPC is prepared by raw materials including the following components in parts by weight: 400-500 parts of cement, 40-50 parts of silica fume, 600-800 parts of fine aggregate, 1000-1200 parts of coarse aggregate, 30-50 parts of steel fiber, 10-30 parts of glass fiber, 120-150 parts of water, and 6-8 parts of water reducing agent;

[0009] The glass fiber is a modified ultrafine glass fiber which is modified by lithium oxide and sodium hydroxide.

[0010] In a second aspect, the method for preparing the above-mentioned UHPC containing glass fiber comprises the following steps:

[0011] S1, adding lithium oxide to glass raw materials and heating and melting them to obtain ultrafine glass fiber raw materials;

[0012] S2, preparing ultrafine glass fiber raw materials into ultrafine glass fibers, and then immersing them in an aqueous solution of sodium hydroxide to obtain modified ultrafine glass fibers;

[0013] S3, mixing the modified ultrafine glass fiber with water to obtain a modified ultrafine glass fiber dispersion;

[0014] S4, mixing cement, silica fume, fine aggregate and coarse aggregate to obtain a first mixture;

[0015] S5, adding the modified ultrafine glass fiber dispersion, water and a water reducing agent to the first mixture, stirring and mixing to obtain a second mixture;

[0016] S6. Add steel fiber to the second mixture, and stir to obtain a UHPC slurry containing glass fiber.

[0017] In a third aspect, the application of the above-mentioned glass fiber-containing UHPC is to use the glass fiber-containing UHPC in the fields of super high-rise buildings, long-span bridges and highways.

[0018] The beneficial effects of the present invention are:

[0019] 1. Glass fiber is added to the present invention, and it is added to concrete together with steel fiber, and the comprehensive performance of ultra-high performance concrete is significantly improved at the macro and micro levels through synergistic effect. Macroscopically, steel fiber provides excellent crack resistance, bending strength and toughness, while modified ultra-fine glass fiber, especially modified ultra-fine glass fiber, effectively controls the initiation and expansion of micro cracks, improves density and impact resistance, and the two together improve the fatigue resistance and durability of concrete. Microscopically, the reasonable aspect ratio design of modified ultra-fine glass fiber can effectively fill the pores in the concrete matrix, reduce porosity and permeability, significantly improve the density of concrete, and optimize the interface transition zone (ITZ), enhance the bonding strength between the matrix and the aggregate, and improve the chemical corrosion resistance of concrete. Steel fiber can further disperse the concentrated stress at the cracks and delay the expansion of cracks from micro to macro. In addition, the ultrafine glass fiber is modified by lithium oxide and sodium hydroxide, which not only significantly improves the durability of the ultrafine glass fiber in a high alkaline environment, but also solves the problem of rapid performance degradation of traditional ultrafine glass fibers due to insufficient chemical stability. It also introduces hydroxyl groups on the fiber surface after modification, so that it forms a strong chemical bond with the cement matrix, enhances the interface adhesion, and improves the structural performance of the interface transition zone. The present invention comprehensively improves the crack resistance, impact resistance and long-term durability of UHPC from macro to micro, and effectively overcomes the defects of the ultrafine glass fiber in the prior art, such as insufficient alkali resistance, poor dispersibility, weak interface bonding and limited microcrack control ability.

[0020] 2. The ultrafine glass fiber in the present invention has been treated with alkaline modification to enhance its ability to resist corrosion in alkaline environments and is less prone to performance degradation. The service life of the fiber in concrete is extended. The modification treatment adds hydroxyl groups to the surface of the ultrafine glass fiber, so that the traditional van der Waals force bonding between the surface of the ultrafine glass fiber and the cement matrix is ​​transformed into hydrogen bonding mainly through hydroxyl groups, thereby significantly enhancing the interfacial adhesion between the fiber and the concrete matrix and optimizing the strength and stability of the interface transition zone (ITZ). The uniform distribution of the fiber in the pores also plays a bridging role, which can not only inhibit the initiation and expansion of microcracks, but also improve the stress transfer path and enhance the overall crack resistance of the concrete. Through the synergistic effect of this interfacial bonding enhancement and pore filling, the modified ultrafine glass fiber significantly improves the impact resistance, fatigue resistance and long-term durability of the concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0022] Figure 1It is a statistical diagram of the compressive strength / elastic modulus and the modified ultrafine glass fiber content of each embodiment and comparative example in the specific implementation manner.

[0023] Figure 2 It is a statistical diagram of the flexural strength / autogenous shrinkage and the content of modified ultrafine glass fiber in each embodiment and comparative example in the specific implementation manner. DETAILED DESCRIPTION

[0024] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0025] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0026] A UHPC containing glass fiber, wherein the raw materials for preparing the UHPC include the following components in parts by weight: 400-500 parts of cement, 40-50 parts of silica fume, 600-800 parts of fine aggregate, 1000-1200 parts of coarse aggregate, 30-50 parts of steel fiber, 10-30 parts of glass fiber, 120-150 parts of water, and 6-8 parts of a water reducing agent; the glass fiber is a modified ultrafine glass fiber modified by lithium oxide and sodium hydroxide.

[0027] The modified ultrafine glass fiber has a diameter of 3-5 μm and a length of 6-20 mm. The modified ultrafine glass fiber is mainly used to fill the pores in the concrete matrix, inhibit the initiation and expansion of microcracks, thereby significantly improving the compactness and impermeability of the concrete. The aluminum oxide tetrahedron content in the ultrafine glass fiber is increased through modification. The aluminum oxide tetrahedron is one of the ligands of Al³⁺ in the glass network and has the function of forming a network. This network structure can significantly improve the mechanical strength and durability of the ultrafine glass fiber. The modifiers lithium oxide and hydroxide in the present invention are Sodium promotes the formation of aluminum oxide tetrahedrons by regulating the chemical environment of glass raw materials; lithium oxide, as a flux, reduces the melting temperature of glass, thereby stably forming more aluminum oxide tetrahedrons at a lower temperature; sodium hydroxide further improves the formation efficiency of aluminum oxide tetrahedrons by adjusting the alkaline environment; by adopting the technical solution of the present invention, the content of aluminum oxide tetrahedrons in ultrafine glass fibers is increased to 30-40% (mass fraction), which can significantly enhance the strength and alkali resistance of ultrafine glass fibers, so that they can maintain long-term stability in a high-alkaline concrete environment.

[0028] Optionally, in the modified ultrafine glass fiber, the mass fraction of lithium oxide is 0.5%~2.0%. Lithium oxide can significantly reduce the melting temperature of glass and increase the melting rate of waste glass. Adding lithium oxide powder to waste glass during high-temperature calcination can improve the strength and hardness of the glass, making it perform better in impact resistance and wear resistance, while also enhancing the durability of the glass.

[0029] Optionally, the cement is silicate cement or ordinary silicate cement with strength grade 52.5 or 52.5R.

[0030] Optionally, the mass percentage of silicon dioxide in the silica ash is not less than 95%, and the volcanic ash activity index is greater than 95%.

[0031] Optionally, the fine aggregate is river sand, and the particle size of the river sand is 0.15~4.75mm.

[0032] Optionally, the coarse aggregate includes sintered bauxite coarse aggregate, and the aggregate crushing index is less than 8.0%.

[0033] Optionally, the steel fiber is a common straight steel fiber.

[0034] Optionally, the water reducer is a polycarboxylic acid-based high-performance water reducer.

[0035] The above-mentioned method for preparing UHPC containing glass fiber comprises the following steps:

[0036] S1, adding lithium oxide to glass raw materials and heating and melting them to obtain ultrafine glass fiber raw materials;

[0037] S2, preparing ultrafine glass fiber raw materials into ultrafine glass fibers, and then immersing them in an aqueous solution of sodium hydroxide to obtain modified ultrafine glass fibers;

[0038] S3, mixing the modified ultrafine glass fiber with water to obtain a modified ultrafine glass fiber dispersion;

[0039] S4, mixing cement, silica fume, fine aggregate and coarse aggregate to obtain a first mixture;

[0040] S5, adding the modified ultrafine glass fiber dispersion, water and a water reducing agent to the first mixture, stirring and mixing to obtain a second mixture;

[0041] S6. Add steel fiber to the second mixture, and stir to obtain a UHPC slurry containing glass fiber.

[0042] Optionally, in S1, the glass raw material is selected from waste glass, and the waste glass is cleaned of surface stains and then air-dried to obtain the glass raw material.

[0043] Optionally, in S1, the mass fraction of lithium oxide is 0.5%~2.0%. During the melting process of the glass raw materials, adding lithium oxide can reduce the melting temperature to 1100℃~1250℃ (about 100℃~200℃ lower than the traditional melting temperature of 1300℃~1400℃), thereby significantly reducing energy consumption and improving melting efficiency; the introduction of lithium oxide can also increase the content of aluminum oxide tetrahedron by adjusting the glass network structure, so that the strength of the prepared modified ultrafine glass fiber reaches 1600~2000MPa, and the hardness is increased to 6~7Mohs, and the impact resistance, wear resistance and durability performance are better.

[0044] Optionally, in S2, the ultrafine glass fiber is placed in a 2-5% mass concentration sodium hydroxide aqueous solution at room temperature (20-25° C.), immersed for 20-60 minutes, and then rinsed and dried; the sodium hydroxide solution is used to remove impurities on the surface of the ultrafine glass fiber and stimulate hydroxyl reaction groups, thereby promoting the hydration reaction of the concrete in subsequent steps.

[0045] Optionally, in S3, the modified ultrafine glass fiber is mixed with water accounting for 65% to 75% of the total water volume, and ultrasonic magnetic stirring is performed for 20 to 40 minutes after mixing.

[0046] Optionally, in S4, the mixing is stirring mixing; the rotation speed of the stirring mixing is 75-85 rpm (low-speed stirring) and the time is 2-3 min; low-speed stirring can prevent powder splashing.

[0047] Optionally, in S5, the first mixture and the modified ultrafine glass fiber dispersion are mixed by stirring, and the stirring speed is 75-85 rpm (i.e., low-speed stirring); and after adding the remaining water and the water reducer, the stirring speed remains unchanged, and stirring is continued for 3-5 minutes to obtain a second mixture.

[0048] Optionally, in S6, after the freshly mixed concrete (i.e., the second mixture) has good fluidity, the steel fiber is slowly added through a square hole sieve; good fluidity means that the cementitious material can be mixed well, and no obvious unhydrated material emerges on the surface of the freshly mixed concrete.

[0049] Optionally, in S6, before adding the steel fiber, the second mixture is stirred at a rotation speed of 155-165 rpm (medium speed stirring) for 3-5 min, and the steel fiber is sieved in while maintaining the stirring state.

[0050] Optionally, the method further includes step S7, casting the UHPC slurry containing glass fibers into a mold, and curing the slurry to a specified age.

[0051] Optionally, in S7, the UHPC slurry containing glass fiber is stirred at high speed (355-365 rpm) for 1-2 min to make its composition uniform, and then poured into shape. During the pouring process, slight vibration is performed for 1-2 min to help remove bubbles and improve the compactness. After pouring, the surface is covered with plastic film to prevent moisture loss, and the film is removed after 24 hours, and cured under standard curing conditions (temperature of 20±2°C, relative humidity>95%RH).

[0052] The application of the above-mentioned glass fiber-containing UHPC is to use the glass fiber-containing UHPC in the fields of super high-rise buildings, long-span bridges and highways.

[0053] Example 1

[0054] A glass fiber-containing UHPC, wherein the raw materials for preparation include the following components in parts by weight: 450 parts of cement, 45 parts of silica fume, 700 parts of fine aggregate, 1,100 parts of coarse aggregate, 40 parts of steel fiber, 10 parts of modified ultrafine glass fiber, 135 parts of water, and 6 parts of water reducing agent (the mass fraction of the modified ultrafine glass fiber is about 0.4% relative to the mass fraction of all the raw materials for preparation);

[0055] The modified ultrafine glass fiber has a diameter of 4±1 μm and an average length of 13 mm; it is modified by lithium oxide and sodium hydroxide, and the mass fraction of lithium oxide in the modified ultrafine glass fiber is 2.0%.

[0056] The cement is ordinary Portland cement with strength grade 52.5.

[0057] The mass percentage of silicon dioxide in silica ash is not less than 95%, and the volcanic ash activity index is greater than 95%.

[0058] The fine aggregate is river sand with a particle size of 0.15~4.75mm, a specific gravity of 2.65, and a fineness modulus of 2.80.

[0059] The coarse aggregate is sintered bauxite coarse aggregate with a maximum particle size of 8 mm, an aggregate crushing index of 8.0%, an elastic modulus of 240 GPa, and a density of 3.2 g / cm 3 .

[0060] The steel fiber is a common straight steel fiber with a length of 13 mm, a diameter of 0.16 mm, a tensile strength greater than 2500 MPa, an elastic modulus of 200 GPa, and a density of 7.8 g / cm 3 .

[0061] The water reducing agent is a polycarboxylic acid-based high-performance water reducing agent.

[0062] The preparation method comprises:

[0063] S1. Clean the surface stains of the collected waste glass and air-dry it to obtain glass raw materials. After crushing the glass raw materials, add them into a high-temperature furnace for calcination and melting. During the melting process, add lithium oxide powder to obtain ultrafine glass fiber raw materials.

[0064] S2. Prepare ultrafine glass fiber from ultrafine glass fiber raw material, soak the obtained ultrafine glass fiber in a 3% mass concentration sodium hydroxide aqueous solution at room temperature (22±1°C) for 25 minutes to ensure that the reaction is fully carried out and avoid excessive surface reaction leading to strength reduction; after the soaking is completed, thoroughly rinse the residual sodium hydroxide solution on the surface of the ultrafine glass fiber with deionized water until the rinse water is neutral, and then dry the ultrafine glass fiber to a moisture content of less than 0.5% to obtain modified ultrafine glass fiber, and perform quantitative analysis through X-ray diffraction (XRD) and nuclear magnetic resonance (NMR) technology, and the mass fraction of aluminum oxide tetrahedron in the obtained modified ultrafine glass fiber is measured to be 36%.

[0065] S3. The modified ultrafine glass fiber is mixed with 75% of the total water, and then subjected to ultrasonic magnetic stirring for 40 minutes to obtain an ultrafine glass fiber dispersion.

[0066] S4. Mix cement, silica fume, fine aggregate and coarse aggregate, and stir at a low speed for 3 minutes to obtain a first mixture.

[0067] S5. Add the modified ultrafine glass fiber dispersion and water to the first mixture, stir at a low speed for 5 minutes, and mix to obtain a second mixture.

[0068] S6. Continue stirring the second mixture at a medium speed. When the second mixture can be well mixed and no unhydrated material is obviously present on the surface of the fresh concrete, keep stirring at a medium speed, slowly add steel fiber through a square hole sieve, and stir evenly at a medium speed to obtain a UHPC slurry containing ultrafine glass fiber.

[0069] S7. The UHPC slurry containing ultrafine glass fiber is stirred at high speed and then poured into a mold. It is slightly vibrated during the pouring process. After the pouring is completed, it is covered with a plastic film and removed after 24 hours. The slurry is cured under standard curing conditions (temperature of 20±2℃, relative humidity>95%RH) to obtain a test block.

[0070] Example 2

[0071] A glass fiber-containing UHPC, wherein the raw materials for preparation include the following components in parts by weight: 450 parts of cement, 45 parts of silica fume, 700 parts of fine aggregate, 1,100 parts of coarse aggregate, 40 parts of steel fiber, 20 parts of modified ultrafine glass fiber, 135 parts of water and 7 parts of water reducing agent (the amount of modified ultrafine glass fiber by weight relative to the total amount of raw materials for preparation is about 0.8%).

[0072] The requirements for each raw material are the same as those in Example 1, and the test block is obtained according to the preparation method of Example 1.

[0073] Example 3

[0074] A glass fiber-containing UHPC, wherein the raw materials for preparation include the following components in parts by weight: 450 parts of cement, 45 parts of silica fume, 700 parts of fine aggregate, 1,100 parts of coarse aggregate, 40 parts of steel fiber, 30 parts of modified ultrafine glass fiber, 135 parts of water and 8 parts of water reducing agent (the amount of modified ultrafine glass fiber by weight relative to the total amount of raw materials for preparation is about 1.2%).

[0075] The requirements for each raw material are the same as those in Example 1, and the test block is obtained according to the preparation method of Example 1.

[0076] Comparative Example 1

[0077] A UHPC without glass fiber is prepared by raw materials comprising the following components in parts by weight: 450 parts of cement, 45 parts of silica fume, 700 parts of fine aggregate, 1100 parts of coarse aggregate, 40 parts of steel fiber, 135 parts of water and 8 parts of water reducing agent.

[0078] The difference from Example 1 is that no modified ultra-fine glass fiber is added.

[0079] The other raw material requirements are the same as those in Example 1, and the test blocks are obtained according to the preparation method of Example 1.

[0080] Comparative Example 2

[0081] A UHPC without glass fiber, wherein the raw materials for preparing the UHPC include the following components in parts by weight: 450 parts of cement, 45 parts of silica fume, 700 parts of fine aggregate, 1100 parts of coarse aggregate, 40 parts of steel fiber, 10 parts of polypropylene fiber, 135 parts of water, and 6 parts of water reducing agent; wherein the specification of the polypropylene fiber is a diameter of 1050 μm, a length of 612 mm, and a tensile strength of 400-600 MPa.

[0082] The difference from Example 1 is that: instead of adding modified ultrafine glass fiber, polypropylene fiber is added; compared with ultrafine glass fiber, polypropylene fiber has a larger diameter, a shorter length, and a lower tensile strength, but has better ductility, and is mainly used to control early plastic shrinkage cracks of concrete rather than to improve long-term mechanical properties; due to the different specific gravities of ultrafine glass fiber and polypropylene fiber, the effect of the polypropylene fiber added here on the fluidity of the slurry during mixing is equivalent to that of 35 parts of modified ultrafine glass fiber.

[0083] The other raw material requirements are the same as those in Example 1, and the test blocks are obtained according to the preparation method of Example 1.

[0084] Comparative Example 3

[0085] A UHPC containing non-modified ultrafine glass fiber, wherein the raw materials for preparation include the following components in parts by weight: 450 parts of cement, 45 parts of silica fume, 700 parts of fine aggregate, 1100 parts of coarse aggregate, 40 parts of steel fiber, 20 parts of non-modified ultrafine glass fiber, 135 parts of water and 6 parts of water reducing agent;

[0086] The difference from Example 2 is that non-modified ultrafine glass fibers are used, that is, the ultrafine glass fibers added in this comparative example are not modified by lithium oxide and sodium hydroxide, and the size is the same as that of the modified ultrafine glass fibers added in Example 1.

[0087] The other raw material requirements are the same as those in Example 1, and the test blocks are obtained according to the preparation method of Example 1.

[0088] Comparative Example 4

[0089] A glass fiber-containing UHPC is prepared by raw materials comprising the following components in parts by mass: 450 parts of cement, 45 parts of silica fume, 700 parts of fine aggregate, 1,100 parts of coarse aggregate, 40 parts of steel fiber, 20 parts of modified ultrafine glass fiber, 135 parts of water and 7 parts of water reducing agent.

[0090] The difference from Example 2 is that: by adjusting the modification process (including: reducing the addition ratio of lithium oxide from 2.0% to 0.8%; reducing the immersion temperature of the ultrafine glass fiber from 22±1°C to 16±1°C, reducing the mass concentration of the sodium hydroxide aqueous solution from 3% to 1.2%, and shortening the immersion time from 25 min to 12 min), the aluminum oxide tetrahedron content of the modified ultrafine glass fiber in this comparative example is controlled and adjusted to a state lower than that of Example 2. In this comparative example, modified ultrafine glass fibers with low aluminum oxide tetrahedron content are added (the actual measured mass fraction of aluminum oxide tetrahedron is 17%).

[0091] The other raw material requirements are the same as those in Example 1, and the test blocks are obtained according to the preparation method of Example 1.

[0092] Comparative Example 5

[0093] A glass fiber-containing UHPC is prepared by raw materials comprising the following components in parts by mass: 450 parts of cement, 45 parts of silica fume, 700 parts of fine aggregate, 1,100 parts of coarse aggregate, 40 parts of steel fiber, 20 parts of ordinary glass fiber, 135 parts of water and 7 parts of a water reducing agent.

[0094] The difference from Example 2 is that ordinary glass fibers with a diameter of 10±2 μm and an average length of 13 are used.

[0095] Performance Testing

[0096] The above-mentioned embodiments and comparative examples were subjected to performance tests, and the results are shown in Table 1, including conventional mechanical properties and autogenous shrinkage properties; wherein, the conventional mechanical properties were measured by test blocks that had completed standard curing (temperature 20±2°C, humidity ≥95%) (28-day compressive strength, flexural strength, etc.), and the autogenous shrinkage properties were measured by the length dimensional change of the test block during the curing process (the size change of the test block was monitored by a micro displacement meter, and the length change from early age to 28 days was recorded).

[0097] Table 1 Performance test results

[0098]

[0099] It can be seen that modified ultrafine glass fiber has a significant effect in improving the performance of ultra-high performance concrete (UHPC). Figure 1 The compressive strength and elastic modulus of Figure 2 From the perspective of the four key indicators of flexural strength and autogenous shrinkage, the introduction of modified ultrafine glass fibers, especially modified ultrafine glass fibers with high alumina tetrahedron content (Examples 2 and 3), is significantly better than the comparison of ordinary ultrafine glass fibers or unmodified ultrafine glass fibers.

[0100] The compressive strength of Example 2 reached 124.6MPa, the elastic modulus was 39.9GPa, the flexural strength reached 15.2kN, and the lowest autogenous shrinkage value was 550μm / m, which shows that the modified ultrafine glass fiber not only significantly improves the mechanical properties of UHPC, but also effectively improves the shrinkage problem. In contrast, the comparative example 1 without adding ultrafine glass fiber and the comparative example 5 with adding ordinary ultrafine glass fiber performed poorly in these indicators, especially the autogenous shrinkage of comparative example 5 was as high as 710μm / m, and the compressive strength and elastic modulus were at the lowest level, reflecting that the ordinary ultrafine glass fiber could not significantly improve the performance of UHPC due to poor alkali resistance and insufficient interface bonding.

[0101] In addition, although the modified ultrafine glass fiber with low aluminum oxide tetrahedron content (Comparative Example 4) is better than the unmodified ultrafine glass fiber in performance, it is still not as effective as the ultrafine glass fiber with high aluminum oxide tetrahedron content in terms of reinforcement, which indicates that the increase in the aluminum oxide tetrahedron content is crucial to the modification effect of the ultrafine glass fiber.

[0102] In general, the use of high-alumina tetrahedron modified ultrafine glass fiber solves the technical problems of poor alkali resistance and weak interface bonding of traditional ultrafine glass fiber, and significantly improves the comprehensive performance of UHPC, especially in mechanical strength, crack resistance and long-term durability. Therefore, this technology has significant application potential in projects that require high-performance concrete.

[0103] The high content of aluminum oxide tetrahedron is achieved through a modification process. By introducing lithium oxide in the preparation process of glass fiber and regulating the chemical environment of the glass raw materials, the formation of aluminum oxide tetrahedron can be significantly promoted. Aluminum oxide tetrahedron is a key component in the glass network structure. A higher content level of aluminum oxide tetrahedron can increase the uniformity and stability of the glass network, thereby improving the strength and durability of the glass fiber.

[0104] The performance improvement effect of alumina tetrahedron is mainly reflected in improving the alkali resistance, mechanical properties and interfacial bonding strength of glass fiber with concrete matrix: glass fiber with higher alumina tetrahedron content shows higher chemical stability in high alkaline environment, and its mass loss rate is significantly lower than that of unmodified glass fiber. The specific values ​​are: the mass loss of the modified ultrafine glass fiber prepared in Example 1 in the 7-day alkali resistance experiment is reduced to less than 1%, while the mass loss of the unmodified glass fiber in Comparative Example 3 can reach more than 5%. The modified ultrafine glass fiber can provide a reinforcement effect in a more stable state; in addition, alumina tetrahedron increases the density of active hydroxyl groups on the surface of glass fiber, thereby enhancing its chemical bonding ability with the concrete matrix and optimizing the strength of the interface transition zone (ITZ). By comparing Example 2 with Comparative Example 3, the compressive strength and flexural strength of UHPC are increased by 3.4% and 12.6%, respectively.

[0105] The technical effect of the modified glass fiber in the present invention is mainly reflected in the significant improvement of its durability and interface bonding strength: the modification process not only improves the alkali resistance of the glass fiber through the synergistic effect of lithium oxide and sodium hydroxide, but also generates evenly distributed hydroxyl groups on its surface. These hydroxyl groups can form a strong chemical bond with the hydration products in the concrete, thereby significantly enhancing the bonding strength between the fiber and the matrix. In the mechanical property test, the UHPC using modified glass fiber, through the comparison between Example 2 and Comparative Example 3, its 28-day compressive strength is improved by 3.4% compared with the unmodified glass fiber, and the flexural strength is improved by more than 12.6%, and the crack resistance and toughness are also significantly improved; the ultrafine glass fiber in the present invention significantly improves the density and impermeability of concrete by filling the micropores in the matrix and inhibiting the initiation and expansion of microcracks; its diameter range is 3~5μm, which is finer than the ordinary glass fiber in Comparative Example 5, and can more effectively fill the fine pores of concrete. Compared with Comparative Example 5, the porosity of Example 2 is reduced by about 5~10%, thereby improving the durability and chemical corrosion resistance of concrete; in addition, the ultrafine glass fiber has excellent bridging performance in microcrack control, and synergizes with ordinary glass fiber to significantly improve the overall performance of UHPC.

[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A UHPC containing glass fiber, characterized in that: The raw materials for preparation include the following components in parts by weight: 400-500 parts of cement, 40-50 parts of silica fume, 600-800 parts of fine aggregate, 1000-1200 parts of coarse aggregate, 30-50 parts of steel fiber, 10-30 parts of glass fiber, 120-150 parts of water, and 6-8 parts of water reducing agent; The glass fiber is a modified ultrafine glass fiber, which is modified by lithium oxide and sodium hydroxide, and the modification method is: adding lithium oxide to glass raw materials and then heating and melting to obtain ultrafine glass fiber raw materials; preparing ultrafine glass fiber from ultrafine glass fiber raw materials, and then immersing in an aqueous solution of sodium hydroxide to obtain modified ultrafine glass fiber; The content of aluminum oxide tetrahedron in the modified ultrafine glass fiber is 30-40% by mass; In the modified ultrafine glass fiber, the mass fraction of lithium oxide is 0.5% to 2.0%.

2. The glass fiber-containing UHPC according to claim 1, characterized in that The modified ultra-fine glass fiber has a diameter of 3-5 μm and a length of 6-20 mm.

3. The glass fiber-containing UHPC according to claim 1, characterized in that The cement is silicate cement or ordinary silicate cement with strength grade 52.5 or 52.5R; The mass percentage of silicon dioxide in the silica ash is not less than 95%, and the volcanic ash activity index is greater than 95%; The fine aggregate is river sand; The coarse aggregate comprises sintered bauxite coarse aggregate; The steel fiber is a common straight steel fiber; The water reducing agent is a polycarboxylic acid-based high-performance water reducing agent.

4. A method for preparing UHPC containing glass fiber according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, adding lithium oxide to glass raw materials and heating and melting them to obtain ultrafine glass fiber raw materials; S2, preparing ultrafine glass fiber raw materials into ultrafine glass fibers, and then immersing them in an aqueous solution of sodium hydroxide to obtain modified ultrafine glass fibers; S3, mixing the modified ultrafine glass fiber with water to obtain a modified ultrafine glass fiber dispersion; S4, mixing cement, silica fume, fine aggregate and coarse aggregate to obtain a first mixture; S5, adding the modified ultrafine glass fiber dispersion, water and a water reducing agent to the first mixture, stirring and mixing to obtain a second mixture; S6. Add steel fiber to the second mixture, and stir to obtain a UHPC slurry containing glass fiber.

5. The method for preparing UHPC containing glass fiber according to claim 4, characterized in that: In S1, the glass raw material is selected from waste glass, and the waste glass is cleaned of surface stains and then air-dried to obtain the glass raw material; in S1, the mass fraction of lithium oxide is 0.5% to 2.0%.

6. The method for preparing UHPC containing glass fiber according to claim 4, characterized in that: In S2, the ultrafine glass fiber is placed in a sodium hydroxide aqueous solution with a mass concentration of 2-5% at room temperature, immersed for 20-60 minutes, and then rinsed and dried.

7. The method for preparing UHPC containing glass fiber according to claim 4, characterized in that: In S3, the modified ultrafine glass fiber is mixed with water accounting for 65-75% of the total water volume, and ultrasonic magnetic stirring is performed for 20-40 minutes after mixing; In S4, the mixing is stirring mixing; the stirring mixing speed is 75-85 rpm, and the time is 2-3 min; In S5, the first mixture and the modified ultrafine glass fiber dispersion are mixed by stirring, and the stirring speed is 75-85 rpm; and after adding the remaining water and the water reducing agent, stirring is continued for 3-5 minutes to obtain a second mixture; In S6, steel fibers are slowly added through a square hole sieve.

8. The method for preparing UHPC containing glass fiber according to claim 4, characterized in that: The method comprises step S7, casting and molding the UHPC slurry containing glass fiber, and curing the slurry to a specified age.

9. The method for preparing UHPC containing glass fiber according to claim 8, characterized in that: In S7, the UHPC slurry containing glass fiber is stirred at high speed for 1 to 2 minutes to make its composition uniform, and then poured into shape, with slight vibration for 1 to 2 minutes during the pouring process; after the pouring is completed, the surface is covered with plastic film to prevent moisture loss, and the film is removed after 24 hours, and cured under standard curing conditions.

10. An application of UHPC containing glass fiber as claimed in any one of claims 1 to 3, characterized in that: The glass fiber-containing UHPC is used in the fields of super high-rise buildings, long-span bridges and highways.

Citation Information

Patent Citations

  • High-performance alkali-resistant glass fiber

    CN103387341A

  • Ultra-high performance concrete as well as preparation method and application thereof

    CN117510158A